2002
DOI: 10.1074/jbc.m207418200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation of Interleukin-8 by β-Catenin-Tcf4

Abstract: Nuclear translocation of ␤-catenin and its association with Tcf/Lef factors are key steps in transduction of the Wnt signal, which is aberrantly activated in a variety of human cancers. In a search for new ␤-catenin-Tcf target genes, we analyzed ␤-catenin-induced alterations of gene expression in primary human hepatocytes, after transduction of either dominant stable ␤-catenin or its truncated, transactivation-deficient counterpart by means of a lentiviral vector. cDNA microarray analysis revealed a limited se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
98
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 52 publications
(50 reference statements)
12
98
1
Order By: Relevance
“…34 This endogenous level of nuclear b-catenin might thus be sufficient to activate the MCP-1 promoter in the presence of TCF-4. In agreement with ours results, Levy et al 32 have shown that, in hepatoma cells containing a constitutively activated bcatenin allele, exogenous wild-type TCF-4 is sufficient to activate the IL-8 promoter. In contrast, the deleted form of TCF-4 which lacks the b-catenin binding domain (DNTCF-4) was unable to activate this promoter.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…34 This endogenous level of nuclear b-catenin might thus be sufficient to activate the MCP-1 promoter in the presence of TCF-4. In agreement with ours results, Levy et al 32 have shown that, in hepatoma cells containing a constitutively activated bcatenin allele, exogenous wild-type TCF-4 is sufficient to activate the IL-8 promoter. In contrast, the deleted form of TCF-4 which lacks the b-catenin binding domain (DNTCF-4) was unable to activate this promoter.…”
Section: Discussionsupporting
confidence: 93%
“…More particularly in agreement with our observations, other chemokines, including IL-8/CXCL8, another angiogenic chemokine, and MCP-3/CCL7, have been shown to be regulated by the b-catenin/TCF pathway. 32,63 The proangiogenic vascular endothelial growth factor (VEGF) has also been shown to be regulated by the b-catenin/TCF pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transduction of GSK3␤-KM also enhanced secretion of IL-8 in early and late EPC. This could be explained by up-regulation of IL-8 by ␤-catenin, which is downstream of GSK3␤ (42). Conversely, GSK3␤-KM promoted the differentiation of late EPC, but early EPC did not exhibit this property.…”
Section: Discussionmentioning
confidence: 97%
“…PDGFB is secreted as vessels develop throughout the limb, leading to the up-regulation of extracellular matrix and connective tissue markers, including Tcf4. In turn, Tcf4 participates in the recruitment of endothelial cells (Levy et al, 2002). As a consequence, a positive feedback loop is generated in which extracellular matrix proteins and Tcf4 are up-regulated along the length of the vessel at the expense of muscle formation.…”
Section: Cleaving the Masses: Generating The Distinct Musclesmentioning
confidence: 99%